The Role of Art Education In Developing Visual Thinking Through The Role-Playing Strategy (Journal of the College of Basic Education, 2026)
This study aims to examine the role of art education in developing visual thinking among intermediate school students through the use of the role-playing strategy as one of the modern teaching methods. Visual thinking is considered one of the essential cognitive abilities that enables students to interpret shapes, symbols, and images, analyze them, and connect them to artistic and cognitive contexts, thereby contributing positively to the enhancement of their creative and innovative skills.The need for this research emerged as most current instructional practices in art education still rely on traditional methods, which often emphasize technical and practical aspects while neglecting students’ cognitive and creative dimensions. The role-playing strategy, however, provides learners with an interactive learning environment that engages them in performing various artistic scenarios, thereby fostering accurate observation, stimulating analytical and interpretive abilities, and enriching visual imagination.The study is conducted within specific spatial, temporal, and human boundaries: it is applied to intermediate school students in the Al-Rusafa First Directorate of Education, Baghdad Governorate, during the 2024–2025 academic year. The research employs an experimental design involving two groups (experimental and control) to measure the effectiveness of the strategy in developing visual thinking using appropriate assessment tools.The significance of this study lies in its theoretical and practical contribution to the educational field, as it highlights the active role of art education in fostering visual thinking skills and opens new pathways for teachers and researchers to adopt modern instructional strategies that enhance students’ creative abilities. Furthermore, the study is expected to guide the educational process toward the integration of interactive methods that strengthen the connection between the artistic and cognitive dimensions, ultimately leading to an improvement in the quality of education in intermediate schools.